Hepatotropic Therapy in Treatment of Liver Injury - D. S. Sukhanov; S. V. Okovityi; P. K. Yablonskyi; T. I. Vinogradova; M. V. Pavlova (Антибиотики и Химиотерапия, 2020)
At present, the conception of the use, efficacy and safety of hepatotropic agents in treatment of drug-induced liver injury, in particular due to antituberculosis drugs is not yet final, which is conditioned by extremely rare clinical trials on the subject adequate to the up-to-date principles of the conclusive medicine. The review presents data on the hepatotoxic effect of antituberculosis drugs, analysis and systematization of the data on the use of hepatotropic agents in liver injury induced by antituberculosis drugs, the principles and characteristics of their clinical use. The mechanism of action of remaxol, a new original hepatotropic agent and the indications of its use are discussed. The experimental findings on the remaxol ability to decrease the antituberculosis drug-induced liver injury through lowering the carbohydrate, albuminous and fatty degeneration and activating the organ reduction are presented. The clinical trials are evident of the most efficient action of remaxol on the signs of toxemia, as well as cytolysis and cholestasis, which along with its antiasthenic and antidepressant action allows to use remaxol as an universal hepatotropic agent in the treatment of diverse drug-induced liver injuries in both the therapeutic and prophylactic schemes.